(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Cancer is the most dangerous disease a human race battles with. Due to which, it is necessity of medicinal chemist to evaluate possible scenario to fight against this disease. The heterocyclic compounds has shown to possess intrinsic diversity and several physicochemical properties. Thus investigation of newer and potential compounds for their activity to resist several malignancies. The present study aims to derivatize four different heterocyclic compounds. The number of members present in the ring has importance in heterocyclic compounds. Thus the six-member ring containing pyrimidine, six-member ring fused with five member ring in indole, bi-penta membered ring containing thiadiazole and one six membered and a penta membered ring containing triazoles have been used in the present study. In the search of potential anti-cancer drugs, several molecules were evaluated and checked for their potency to interact with a cancer target enzyme Vascular endothelial growth factor receptor 2 (VEGFR2). This study involves detailed in-silico analysis of several compounds and indicates compounds having potential ability to resist this enzymes and hence the anti-cancer agent.